Teachers’ Perception of Social Studies as an Instrument for Promoting Peaceful Coexistence in Nigeria - Omiyefa, Muraina Olugbenga (International Journal of Contemporary Studies in Education, 2024)
This study examined the teachers' perception of Social Studies as an instrument for achieving peaceful coexistence in Nigeria. The study adopted the descriptive research design with population comprising Social Studies teachers in both private and public secondary schools in Nigeria. The sample consisted 100 respondents selected using a multistage sampling procedure. The instrument used for the study was a self-constructed questionnaire titled “Perception of Social Studies for Peaceful Coexistence Questionnaire” (PSSPCQ) which was validated by experts. The reliability was established at 0.78 co-efficient. Frequency and percentages were used to analyse the research questions and t-test was used for the hypotheses generated. The study showed that Social Studies is effective in achieving peaceful coexistence by tolerating each other, preparing individuals through the acquisition of knowledge, attitude, values and skills necessary for social and civic responsibilities. Results also indicated that there was significant difference in the perception of teachers on the relevance of Social Studies in achieving peaceful coexistence based on school type and religion. The study therefore, recommended that Social Studies should also be taught at all levels of the Nigerian school system to ensure that the citizenry has all needed information needed for peaceful coexistence.